Shirodhara: A psycho-physiological profile in healthy volunteers - Dhuri, Kalpana D. (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Shirodhara is a classical and a well-established ayurvedic procedure of slowly and steadily dripping medicated oil or other liquids on the forehead. This procedure induces a relaxed state of awareness that results in a dynamic psycho-somatic balance. OBJECTIVES: The objective of the study is to evaluate the psychological and physiological effects of Shirodhara in healthy volunteers by monitoring the rating of mood and levels of stress, electrocardiogram (ECG), electroencephalogram (EEG), and selected biochemical markers of stress. MATERIALS AND METHODS: The study was conducted in the human pharmacology laboratory. The study design was open labeled, comparing the baseline variables with values after Shirodhara. The subjects (n = 16) chosen were healthy human volunteers who gave an informed consent. Shirodhara was preceded by Abhyanga – whole body massage. The Shirodhara method was standardized for rate of dripping with peristaltic pump and temperature was controlled with a thermostat. Mood and stress levels were assessed by validated rating scales. The pre- and post-Shirodhara ECG and EEG records were evaluated. RESULTS: Student's paired “t” test was applied to the means + SE of the variables to calculate statistical significance at P <0.05. There was a significant improvement in mood scores and the level of stress (P <0.001). These changes were accompanied by significant decrease in rate of breathing and reduction in diastolic blood pressure along with reduction in heart rate. The relaxed alert state, after Shirodhara, was co-related with an increase in alfa rhythm in EEG. CONCLUSION: A standardized Shirodhara leads to a state of alert calmness similar to the relaxation response observed in meditation. The clinical benefits observed with Shirodhara in anxiety neurosis, hypertension, and stress aggravation due to chronic degenerative diseases could be mediated through these adaptive physiological effects.